Potential therapeutic targets for growth arrest of colorectal cancer cells exposed to PTHrP. (15th December 2018) - Martín, María Julia; Gigola, Graciela; Zwenger, Ariel; Carriquiriborde, Martín; Gentil, Florencia; Gentili, Claudia
Abstract: Although PTHrP is implicated in several cancers, its role in chemoresistance is not fully elucidated. We found that in CRC cells, PTHrP exerts proliferative and protective effects and induces cell migration. The aim of this work was to further study the effects of PTHrP in CRC cells. Herein we evidenced, for the first time, that PTHrP induces resistance to CPT-11 in Caco-2 and HCT116 cells; although both cell lines responded to the drug through different molecular mechanisms, the chemoresistance by PTHrP in these models is mediated through ERK, which in turn is activated by PCK, Src and Akt. Moreover, continue administration of PTHrP in nude mice xenografts increased the protein levels of this MAPK and of other markers related to tumorigenic events. The understanding of the molecular mechanisms leading to ERK 1/2 activation and the study of ERK targets may facilitate the development of new therapeutic strategies for CRC treatment. Highlights: PTHrP activates ERK pathway through PKC, Scr and Akt in CRC cells. PTHrP induces resistance to Irinotecan in Caco-2 and HCT116 cells. The chemoresistance by PTHrP in CRC cells is mediated through ERK. PTHrP administration increases ERK protein levels in nude mice xenografts. In vivo PTHrP modulates markers related to tumorigenic events of CRC.